Variability in Chakkarakolli (gymnema sylvestrwe R.BR.) using morphological, biochemical nad molecular markers - Smitha Nair (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2005)
Plants represent an unparalleled source for drug development. Plant based natural products play a dominant role in the pharmaceutical industry. Plant based remedies are available for a number of different health problems. In today’s scenario, diabetes is one of the most common non-communicable diseases globally and is also the fourth major cause of death in most developed countries. So the demand for natural alternatives to blood sugar control is ever increasing. Several indigenous medicinal plants have been indicated in the Ayurveda system of medicine to possess antidiabetic activity. Native to the forests of South India, Gymnema sylvestre R.Br. is known for its hypoglycaemic property from the time immemorial. Practitioners of Ayurveda first used Gymnema to treat diabetes almost 2000 years ago. Keeping in view the importance of this medicinal plant, a study was conducted to identify the variability in Gymnema accessions collected and maintained at the Centre for Plant Biotechnology and Molecular Biology.